2016
DOI: 10.1055/s-0036-1592103
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Anthropometric Indicators in the Prediction of Urinary Incontinence in Physically Active Older Women

Abstract: Purpose To determine the diagnostic accuracy and the cutoff point of the variables conicity index, waist to height ratio and fat percentage to detect urinary incontinence in physically active older women. Method A total of 152 women were analyzed. The instruments used were the International Physical Activity Questionnaire (IPAQ [Area 4]) to check the level of physical activity, and the Diagnostic Form to obtain sociodemographic data and presence of urinary incontinence. To calculate the conicity index, waist t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Besides this, cut-off points of other anthropometric indicators have been observed when detecting SUI. 24 These authors identified that values above 1.23 for the taper index, 0.55 for waist-to-height ratio, and 39.71 for body fat percentage may detect SUI. Another study obtained cut-off points of 25.82 kg/m 2 for BMI, 78.50 cm for WC, 0.84 for WHR to detect UI, but none of these indicators had an area under the ROC curve greater than 0.7 suggesting limitation in only one indicator to predict UI.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, cut-off points of other anthropometric indicators have been observed when detecting SUI. 24 These authors identified that values above 1.23 for the taper index, 0.55 for waist-to-height ratio, and 39.71 for body fat percentage may detect SUI. Another study obtained cut-off points of 25.82 kg/m 2 for BMI, 78.50 cm for WC, 0.84 for WHR to detect UI, but none of these indicators had an area under the ROC curve greater than 0.7 suggesting limitation in only one indicator to predict UI.…”
Section: Discussionmentioning
confidence: 99%
“…A previous cross‐sectional study demonstrated that overall obesity is a strong risk factor for UI . The largest cross‐sectional population‐based study that enrolled 28 000 women reported that the association between BMI and UI was strong and that there was a dose–response effect of BMI on the prevalence of UI .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which obesity is related UI is theorized to be an obesity‐induced increase in abdominal pressure that, in turn, increases bladder pressure and urethral mobility, leading to stress UI, as well as exacerbating detrusor instability and overactive bladder . Overall obesity parameters, such as body weight or body mass index (BMI), are related to UI . In addition, central obesity parameters, such as waist circumference or the waist : hip ratio, have been shown to be related to UI .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat intake directly regulates systemic energy metabolism and affects body weight [ 13 ]. According to previous studies, obesity is linked to UI through increased abdominal pressure, weak pelvic muscles, and pelvic innervation disorder [ [14] , [15] , [16] , [17] , [18] ]. The effect of fat intake on UI may be mediated by body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%